Role of poly (ADP-ribose) polymerase-1 and NF-kappaB as potential risk factor in the development of non-small cell lung cancer in Chinese individuals - Anguo Chen; Zaicheng Yu; Renquan Zhang; Qihong Zhao; Jianjun Ge (Bangladesh Pharmacological Society, 2018)
The objective of this study was to evaluate the role of poly (ADP-ribose) polymerase-1 (PARP-1) and NF-kappaB as potential risk factor in the development of non-small cell lung cancer in Chinese individuals (n=110) of either gender aged <65 years. Healthy Chinese individuals (n=110) were included as control. Polymerase chain reaction was used to determine the role of PART-1 and NF-kappaB using plasma sample. The individuals with the GA genotype and carrier of G allele were at high-risk of non-small cell lung cancer. There was involvement of dL/is of the NF-kappaB in non-small cell lung cancer. Our study result suggests that the PARP-1 and NF-kappaB play an important role in development of non-small cell lung cancer in China.